Water and oil repellent properties affected by the crystallinity of fluorocarbon chain in fluorine-silicon containing finishing agent. Issue 3 (3rd March 2020) - Li, Qing; Fan, Zenglu; Chen, Chuangxun; Li, Zhibin
Abstract: Novel soap free and core-shell typed fluorosilicon containing water and oil-repellent finishing agents were fabricated via semi-continuous seed emulsion polymerization reaction. Notably, a series of non-functional acrylate monomers with different carbon chain lengths, i.e. methyl methacrylate, ethyl methacrylate, butyl methacrylate, iso-Octyl methacrylate and lauryl methacrylate were deployed to tune the crystallinity and ordering of final polymer membranes. Experimental results reveal that the water and oil-repellent properties of treated cotton fabric were significantly affected by the crystallinity of designed products. Physical and chemical characterizations were carried out via infrared spectroscopic analysis, thermogravimetric analysis, X-ray diffraction, scanning electron microscope and transmission electron microscope techniques. The hydrostatic pressure, water contract angle, moisture resistance and oil-repellent rating of cotton fabric treated by best performed finishing agent (adopting lauryl methacrylate as non-functional monomers) were determined to be 2.87 KPa, 144.6°, 4 and 5 grade, respectively.